2009
DOI: 10.1016/j.jce.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurs' gender and financial constraints: Evidence from international data

Abstract: This paper studies gender discrimination against entrepreneurs by financial institutions. Based on the Business Environment and Enterprise Performance Survey (BEEPS) that covers firms in several countries of Western Europe as well as in the transition countries of Eastern Europe, our analysis suggests that femalemanaged firms are less likely to obtain a bank loan compared with male-managed counterparts. In addition, there is some evidence that female entrepreneurs are charged higher interest rates when loan ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
284
4
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 381 publications
(319 citation statements)
references
References 48 publications
23
284
4
8
Order By: Relevance
“…Muravyev, Schafer and Talavera (2007) show that once controls are introduced, there is a significant difference in the interest rate paid by men v. women.…”
Section: Are Women's Firms Constrained To Be Small?mentioning
confidence: 97%
See 2 more Smart Citations
“…Muravyev, Schafer and Talavera (2007) show that once controls are introduced, there is a significant difference in the interest rate paid by men v. women.…”
Section: Are Women's Firms Constrained To Be Small?mentioning
confidence: 97%
“…Muravyev, Schafer and Talavera (2007) have shown that women are (5.4%) less likely than men to get a loan, when correcting for selection on whether the firm needs a loan, and controlling for the profit of the firm, capacity utilization, age, and competition faced by the firm, as well as industry and country fixed effects. They note the importance of controlling for capacity utilization and age; if women are operating firms that are younger and at lower capacity utilization than men 19 and this could influence the financial decisions of bankers.…”
Section: Are Women's Firms Constrained To Be Small?mentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-country empirical study by Muravyev et al (2009) found that, compared to male-managed companies, female-managed companies were less likely to get formal credit; hence, the coefficient of this variable is expected to have a negative sign. Regional dummy variables are used to reflect the higher per capita income level in Tashkent, the capital city and financial centre of the country.…”
Section: Do Interpersonal Relations Matter In Gaining Access To Formamentioning
confidence: 99%
“…Consequently, two alternative models with different sub-samples are estimated to deal with the issue. The first sub-sample is conditioned upon applying for formal finance, and the second conditioned upon expressing a need for external finance (Cavaluzzo et al, 2002;Blanchard et al, 2008;Muravyev et al, 2009). …”
mentioning
confidence: 99%